2011
DOI: 10.1002/jcb.23225
|View full text |Cite
|
Sign up to set email alerts
|

Sensory nerve induced inflammation contributes to heterotopic ossification

Abstract: Heterotopic ossification (HO), or bone formation in soft tissues, is often the result of traumatic injury. Much evidence has linked the release of BMPs (bone morphogenetic proteins) upon injury to this process. HO was once thought to be a rare occurrence, but recent statistics from the military suggest that as many as 60% of traumatic injuries, resulting from bomb blasts, have associated HO. In this study, we attempt to define the role of peripheral nerves in this process. Since BMP2 has been shown previously … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
195
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 135 publications
(201 citation statements)
references
References 68 publications
(93 reference statements)
6
195
0
Order By: Relevance
“…Since these cells are behind the blood-nerve barrier [26], it is difficult to envision how BMP2 enters this location. However, the timing appears to be similar to induction of the neuro-inflammatory pathways previously described [12, 14]. The lack of PS + cells in the soft tissues outside the nerve may be a direct result of rapid binding of BMP2 by inhibitory binding proteins in the region [27].…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Since these cells are behind the blood-nerve barrier [26], it is difficult to envision how BMP2 enters this location. However, the timing appears to be similar to induction of the neuro-inflammatory pathways previously described [12, 14]. The lack of PS + cells in the soft tissues outside the nerve may be a direct result of rapid binding of BMP2 by inhibitory binding proteins in the region [27].…”
Section: Discussionmentioning
confidence: 65%
“…In addition to accessory cells migrating from the perineurial layer, cells within the endoneurium or axon compartment were found to express the osteoblast-specific factors SP7 and Dlx5 [12] [13]. These SP7 + Dlx5 + cells exit the nerve through the endoneurial vessels and are deposited at the site of new bone formation [7].…”
Section: Introductionmentioning
confidence: 99%
“…Given the known mechanism of action of BTxA (inhibition of neurotransmitter release), we therefore speculated that the blockade of neuromuscular signaling by BTxA inhibits neuromuscular interactions integral to the osteogenic response elicited by musculoskeletal trauma. Furthermore, because fracture healing and HO share common initiating events (including inflammation and BMP signaling) [17,27,30,32], we also speculated that BTxA-induced muscle paralysis would prevent the formation of heterotopic bone. However, interpreting the precise mechanism by which muscle paralysis inhibits osteogenesis in the rat fracture model is confounded by the heterogeneity of the tissue response, soft tissue injury, and modified gait kinematics, all of which can alter the observed cellular responses.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies have shown that the polyamines spermine and spermidine are an essential part of the granule component of mast cells, and play an essential role in the biogenesis and homeostasis of these organelles [Garcia‐Faroldi et al, 2010]. We have previously shown that mast cells are a critical component of HO and when these cells are eliminated HO is severely inhibited [Salisbury et al, 2011]. Therefore, spermine and spermidine may participate in the function of mast cells during HO.…”
Section: Discussionmentioning
confidence: 99%
“…This model involves both changes in BMP signaling, because of BMP2 production, as well as inflammation because of delivery of the adenovirus‐transduced cells. Characterization of this model, shows one of the first changes in the tissues is in peripheral nerves [Salisbury et al, 2011, 2012; Lazard et al, 2015], followed by the release of cells from the perineurial layer of the adjacent peripheral nerves of cells that express uncoupling protein 1 (UCP1) [Olmsted‐Davis et al, 2007]. UCP1 is thought to be the hallmark of brown adipocytes, and further characterization of these cells suggest they match almost identically brown adipocytes present in depots, with the exception that they lack expression of PMDR16 [Salisbury et al, 2012].…”
mentioning
confidence: 99%